Preparation, Characterization, and Tetracycline Adsorption Efficiency of Tea Residue-Derived Activated Carbon - Faisal, Hala A.; Mohammed, Alaa Kareem; Hussin AL Sbani, Nadya; Wan Isaha, Wan Nor Roslam (Al-Khwarizmi Engineering Journal, 2023)
The process for preparing activated carbon (AC) made from tea residue was described in this paper. Investigated were the physicochemical characteristics and adsorption efficiency of the produced AC. Activation with potassium hydroxide (KOH) and carbonization at 350 °C are the two key steps in the manufacturing of AC. The activated carbon was used to adsorb Tetracycline (TC). Different parameters were studied at room temperature to show their effects on the adsorption efficiency of TC. These parameters are the initial concentration of adsorbate TC, solution acidity pH, time of adsorption, and adsorbent dosage. The prepared active carbon was characterized using Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), X-ray diffraction (XRD), and Brunauer-Emmett-Teller (BET). The equilibrium of TC adsorption on the tea-activated carbon TAC is effectively represented by the Langmuir model. Tetracycline could be adsorbed onto the prepared activated carbon with a maximum capacity of 45.662 mg g-1. Adsorption kinetics are well represented by pseudo-second-order. The investigation of adsorption thermodynamics demonstrates that TC adsorption on TAC is endothermic and spontaneous